Curable composition, cured product, and article
A curable composition with 2-(meth)allyloxymethylacrylate ion and water-resistant components addresses the challenge of balancing hydrophilicity and water resistance, producing a durable, water-insoluble hydrophilic layer for diverse applications.
Patent Information
- Application Number
- JP2023108665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Existing curable compositions that form hydrophilic layers on surfaces struggle with achieving a balance between hydrophilicity and water resistance, particularly due to the water-soluble nature of (meth)acrylic acid salts, which hinder film formation and limit their application.
A curable composition containing 2-(meth)allyloxymethylacrylate ion, a hydrophilic cation, and specific water resistance improving components, such as water-resistant polyvalent metal ions and surfactants, is developed to enhance both hydrophilicity and water resistance through radical polymerization and intermolecular interactions.
The composition results in a cured product with excellent hydrophilicity and water resistance, suitable for various applications, including everyday items and medical equipment, by forming a durable, water-insoluble hydrophilic layer that maintains its properties under exposure to moisture.
Smart Images

Figure 2025007342000001 
Figure 2025007342000002 
Figure 2025007342000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable composition that forms a hydrophilic surface, a cured product obtained by curing the composition, and an article having the cured product. [Background technology]
[0002] It is known that forming a hydrophilic layer with a certain level of water and moisture resistance on the surface of an article can provide anti-fogging, anti-fouling, anti-static, antibacterial, etc. Such hydrophilic layers are used in a variety of fields, from everyday items such as glasses, helmets, bathroom mirrors, automobile lamps, heat exchangers for air conditioners, camera lenses, and endoscopes, to building materials, transportation equipment, home appliances, precision electronic equipment, and medical equipment.
[0003] Known methods for forming the above-mentioned hydrophilic layer on the surface of an article include a method of thermoplastically molding a thermoplastic resin kneaded with a hydrophilizing agent, a method of hydrophilizing the resin surface by chemical treatment such as alkali treatment, a method of coating and curing a curable composition that produces a hydrophilic cured product on the surface, a method of forming a fine three-dimensional structure or unevenness on the surface by a method such as nanoimprinting, etc. Among them, the method of coating and curing a curable composition that produces a hydrophilic cured product on the surface is a widely used method because it can form a hydrophilic layer on the surface of various articles using a relatively simple device.
[0004] In order to achieve a certain level of water and moisture resistance, most curable compositions that produce hydrophilic cured products contain reactive compounds that form covalent crosslinks, or the reactive compounds themselves have hydrophilic structures, or contain hydrophilic non-reactive substances, surfactants, etc. As hydrophilic inorganic substances, inorganic oxide particles such as silica and alumina are often used.
[0005] In addition, various structures have been proposed as hydrophilic structures possessed by hydrophilic organic substances, such as sulfonate structures (e.g., Patent Document 1), polyhydric alcohol structures (e.g., Patent Document 2), betaine structures (e.g., Patent Document 3), polyethylene glycol structures (e.g., Patent Document 4), and polyacrylamide structures (e.g., Patent Document 5), and various organic low-molecular, oligomer, and polymer compounds having such hydrophilic structures are used. Carboxylate structures have also been proposed and used as hydrophilic structures, and many forms have been proposed in which polymer compounds having carboxylate structures are used as components of curable compositions, such as a form in which a carboxylate polymer is crosslinked with a crosslinking agent (e.g., Patent Document 6) or a form in which a carboxylate polymer is added as a water-absorbing substance (e.g., Patent Document 7).
[0006] On the other hand, as a highly polymerizable carboxylate, a salt of (meth)acrylic acid is widely used for various applications, but it is water-soluble and dissolves only in highly polar organic substances, and is a powdery substance without a solvent that has no film-forming properties, making it difficult to use as a curing component of a curable composition that is applied to and cured on the surface of an article. A salt of 2-(meth)allyloxymethylacrylic acid has been proposed as a highly polymerizable carboxylate that can solve this problem. This salt is compatible with various organic substances and has film-forming properties even in a solvent-free state, and therefore has been shown to be applicable to a variety of applications (e.g., Patent Documents 8 to 10). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 054877 [Patent Document 2] JP 2011-213904 A [Patent Document 3] International Publication No. 2017 / 018146 [Patent Document 4] JP 2007-063325 A [Patent Document 5] JP 2012-007033 A [Patent Document 6] Patent Publication No. 2021-066785 [Patent Document 7] International Publication No. 2016 / 021458 [Patent Document 8] JP 2012-107208 A [Patent Document 9] JP 2013-216737 A [Patent Document 10] JP 2013-231164 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described above, cured products having hydrophilicity and water resistance are used in a variety of applications, and there is a demand for new materials capable of forming cured products having excellent properties required for various applications. In view of the above-mentioned current situation, an object of the present invention is to provide a novel composition capable of forming a cured product having water resistance and hydrophilicity. [Means for solving the problem]
[0009] As a result of extensive investigations conducted by the present inventors in order to achieve the above-mentioned object, they discovered that a cured product having excellent water resistance and hydrophilicity can be obtained by preparing a curable composition containing a 2-(meth)allyloxymethylacrylate ion, a hydrophilic cation, and a specific water resistance improving component, and thus completed the present invention. That is, the present invention is described in the following [1] to [4]. [1] Formula (1):
[0010] [ka]
[0011] (In the formula, R represents a hydrogen atom or a methyl group.) a hydrophilic cation, and a water resistance improving component, the water resistance improving component comprising at least one member selected from the group consisting of a water-resistant polyvalent metal ion, a radical polymerizable compound having a hydrophilic functional group or structure, a polyfunctional radical polymerizable compound, a low-viscosity radical polymerizable compound, a compound that undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group, and a resin having a hydrophilic functional group or structure. [2] The curable composition according to [1] above, further comprising a surfactant. [3] A cured product of the curable composition described in [1] or [2] above. [4] A cured product of the curable composition according to the above [1] or [2], A water-insoluble cured product characterized by satisfying at least one of the following index (I) or index (II): Index (I) Shows anti-fogging properties against exhaled air Indicator (II) Water contact angle is 50° or less [5] An article having, on its surface, the cured product according to [3] above or the water-insoluble cured product according to [4] above. Effect of the Invention
[0012] The curable composition of the present invention provides a cured product having excellent water resistance and hydrophilicity. By forming a cured product on the surface of an article using the curable composition of the present invention, it is possible to impart hydrophilicity to the surface of the article. The curable composition of the present invention can be used in various fields, from daily necessities, building materials, transport equipment, home appliances, precision electronic equipment to medical equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] A preferred embodiment of the present invention will be specifically described below, but the present invention is not limited to the following description, and can be appropriately modified and applied within the scope of the present invention. A combination of two or more of the individual preferred embodiments of the present invention described below also falls within the preferred embodiment of the present invention. In addition, (meth)acrylic means acrylic or methacrylic. (meth)acrylate means acrylate or methacrylate. (meth)acryloyl means acryloyl or methacryloyl. (meth)allyl means allyl or methallyl.
[0014] <Curable composition> The curable composition of the present invention is represented by the following formula (1):
[0015] [ka]
[0016] (In the formula, R represents a hydrogen atom or a methyl group.) a hydrophilic cation, and a water resistance improving component, wherein the water resistance improving component includes at least one member selected from the group consisting of a water-resistant polyvalent metal ion, a radical polymerizable compound having a hydrophilic functional group or structure, a polyfunctional radical polymerizable compound, a low-viscosity radical polymerizable compound, a compound that undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group, and a resin having a hydrophilic functional group or structure.
[0017] The curable composition of the present invention can give a cured product with excellent hydrophilicity. The reason is presumed to be as follows. That is, 2-(meth)allyloxymethylacrylic acid ion has a linear molecular structure having a hydrophobic ether group ((meth)allyl ether group) before polymerization, but upon radical polymerization, it is cyclized to form a cyclic ether (a tetrahydrofuran ring in the case of an allyl ether group, and a tetrahydropyran ring in the case of a methallyl ether group), and the polarity increases compared to before polymerization. Furthermore, since it contains a hydrophilic cation, it has excellent hydrophilicity. On the other hand, since the structure is one in which a cyclic ether is included in the main chain upon polymerization, the solubility in various liquid media decreases. Furthermore, water resistance is improved by containing one or more of a water-resistant polyvalent metal ion, a radical polymerizable compound having a hydrophilic functional group or structure, a polyfunctional radical polymerizable compound, a low-viscosity radical polymerizable compound, a compound that undergoes a thermal addition reaction or thermal condensation reaction with an active hydrogen group, and a water resistance improving component having a hydrophilic functional group or structure.
[0018] [2-(meth)allyloxymethylacrylic acid ion] The curable composition of the present invention contains a 2-(meth)allyloxymethyl acrylate ion represented by the above formula (1). The 2-(meth)allyloxymethyl acrylate ion is a cyclopolymerizable carboxylate ion, and undergoes cyclopolymerization under radical polymerization conditions. Before polymerization, the molecular structure is linear with a hydrophobic ether group ((meth)allyl ether group), but after radical polymerization, it is cyclized to form a cyclic ether (a tetrahydrofuran ring in the case of an allyl ether group, and a tetrahydropyran ring in the case of a methallyl ether group), and the polarity increases compared to before polymerization. On the other hand, since the structure becomes one in which a cyclic ether is included in the main chain upon polymerization, the solubility in various liquid media decreases.
[0019] [Other anions] The curable composition may contain only the 2-(meth)allyloxymethyl acrylate ion as the anion, or may contain anions other than the 2-(meth)allyloxymethyl acrylate ion. The other anion may be either an inorganic anion or an organic anion, but from the viewpoint of solubility in organic substances, an organic anion is preferred, and from the viewpoint of radical polymerizability, a carboxylate ion having a double bond conjugated with a carboxy group is preferred.
[0020] Examples of the carboxylate ion having a double bond conjugated with the carboxy group include a (meth)acrylate ion and a carboxylate ion of a terminally carboxylated (meth)acrylic acid ester (2-carboxyethyl acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 3-carboxypropyl (meth)acrylate). One or more of these may be appropriately selected depending on the purpose and application.
[0021] [Hydrophilic cation] The hydrophilic cation contained in the curable composition is preferably at least one cation selected from the group consisting of cations of Group 1 elements of the periodic table, cations of Group 2 elements of the periodic table, and cations containing non-metallic elements of Group 15 elements of the periodic table.
[0022] Preferable examples of the cations of Group 1 elements of the periodic table and cations of Group 2 elements of the periodic table include lithium ions, sodium ions, potassium ions, magnesium ions, calcium ions, and barium ions.
[0023] Examples of the cations containing nonmetallic elements of Group 15 of the periodic table include ions in which a nitrogen atom is cationized (ammonium ion, protonated amine, quaternary ammonium ion) and ions in which a phosphorus atom is cationized (phosphonium ion, protonated phosphine, quaternary phosphonium ion). Among these, from the viewpoints of biological safety and availability, ions in which a nitrogen atom is cationized are more preferred.
[0024] The protonated amine includes an amine having a proton (H+) added thereto to form a cation. The amine may be any of primary, secondary and tertiary amines, with primary or secondary amines being preferred from the viewpoint of enhancing hydrophilicity, and tertiary amines being preferred from the viewpoint of improving compatibility with low-polarity compounds. The amine has no particular limitation on its valence, and a smaller valence is preferred from the viewpoint of decreasing the viscosity of the curable composition, while a larger valence is preferred from the viewpoint of improving water resistance. The number of carbon atoms in the amine is preferably 3 to 200, more preferably 4 to 150, and even more preferably 5 to 100, from the viewpoints of improving compatibility with other components in the curable composition and the viscosity of the curable composition.
[0025] Specific examples of the above amines, in terms of the names of the amines before protonation, include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethanolamine, diethanolamine, triethanolamine, tris(2-aminoethyl)amine, hexamethylenediamine, iminobispropylamine, methyliminobispropylamine, 3,6,9,12-tetraoxa-tetradecane-1,14diamine, ethylenediamine, trishydroxymethylaminomethane, N,N'-bis(2-hydroxyethyl)ethylenediamine, 1,3-bisaminomethylcyclohexane, 1,4-bisaminomethylcyclohexane, 3-aminomethyl-3,5,6-trimethylcyclohexylamine, isophoronediamine, 2,5 (or 2,6)-bis(aminomethyl)bicyclo[2,2,1]heptane, 2,6 (or 2,7)-bis(aminomethyl)bicyclo[3,2,1] Octane, 2,5 (or 2,6)-bis(aminomethyl)-7-dimethylbicyclo[2,2,1]heptane, 2,6-bis(aminomethyl)adamantane, m-xylylenediamine, p-phenylenediamine, bis(4-aminophenyl)methane, 1,4 (or 2,6 or 2,7)-bis(aminomethyl)naphthalene, diallylamine, piperazine, aminoethylpiperazine, bisaminopropylpiperazine, 2,4,6-triamino-1,3,5-triphenylamine, Examples of the silane include riazine, 2-methylimidazole, 2-ethyl-4-methylimidazole, diazabicycloundecene, diazabicyclononene, diazabicyclooctane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, polyethyleneimine, and diallylamine polymers.
[0026] Specific examples of the quaternary ammonium ion include a tetramethylammonium ion, a tetraethylammonium ion, a tetrabutylammonium ion, a benzyltrimethylammonium ion, and a hexadecyltrimethylammonium ion.
[0027] [Other cations] The curable composition may contain only the above-mentioned hydrophilic cations as cations, but may also contain one or more other types of cations. Examples of the other cations include metal ions or metal oxide ions of elements in Groups 3 to 15 of the periodic table. Specific examples include metal ions or metal oxide ions of transition metal elements such as lanthanum, zirconium oxide, iron, cobalt, nickel, and copper; metal ions or metal oxide ions of typical metal elements in Groups 12 to 15 of the periodic table such as zinc, aluminum, tin, lead, and bismuth; and combinations of two or more of these may also be used. From the viewpoint of making the cured product of the present invention colorless and improving water resistance, ions of metals or metal oxides belonging to typical metal elements, Group 3 elements of the periodic table, or Group 4 elements of the periodic table are preferred, and from the viewpoints of availability and biological safety, metal or metal oxide ions of zirconium, zirconium oxide, zinc, and aluminum are more preferred, and zinc ions are even more preferred.
[0028] As a method for analyzing the content of the above-mentioned anions and cations, ion chromatography and capillary electrophoresis are preferred from the viewpoint of direct detection as ions, and from the viewpoint of performing measurement in a short time, 1 H-NMR is preferred. Among them, capillary electrophoresis is preferred from the viewpoints of sensitivity, ease of measurement, and ease of maintenance of the apparatus.
[0029] The content of the 2-(meth)allyloxymethylacrylic acid ion in the curable composition is preferably 3 to 90 mass%, more preferably 5 to 85 mass%, and even more preferably 10 to 80 mass%, based on 100 mass% of the curable composition.
[0030] The content of the hydrophilic cation in the curable composition is preferably 0.5 to 50 mass%, more preferably 1 to 40 mass%, and even more preferably 2 to 30 mass%, based on 100 mass% of the curable composition.
[0031] The curable composition contains the above-mentioned anionic component and cationic component, and may contain these components as a salt compound formed from these ions. That is, the curable composition may contain a salt compound formed from an anionic component containing at least the above-mentioned 2-(meth)allyloxymethylacrylic acid ion and a cationic component containing at least the above-mentioned hydrophilic cation. The anion component and the cation component forming the above salt compound may further contain other anions and cations as described above. The curable composition may contain one or more of the above salt compounds.
[0032] A preferred method for generating the anion and cation contained in the curable composition is a method of neutralizing one or more protonic acids including at least 2-(meth)allyloxymethylacrylic acid with one or more bases. The protonic acid may be completely or partially neutralized, and when partially neutralized, a mixture of a salt compound and a protonic acid is generated.
[0033] Examples of the base include inorganic bases such as hydroxides and oxides of metal elements belonging to Groups 1 to 15 of the periodic table, and organic bases containing non-metal elements of Group 15 of the periodic table, such as ammonia, amines, and ammonium hydroxide. The neutralization can be carried out by any known method without any particular limitation.
[0034] [Water resistance improving ingredient] The curable composition contains, as the water resistance improving component, one or more of a water-resistant polyvalent metal ion, a radical polymerizable compound having a hydrophilic functional group or structure, a polyfunctional radical polymerizable compound, a low-viscosity radical polymerizable compound, a compound that undergoes a thermal addition reaction or thermal condensation reaction with an active hydrogen group, and a resin having a hydrophilic functional group or structure. The curable composition preferably contains two or more of these components, and more preferably contains three or more of them. The combination of two or more kinds may be appropriately selected according to the application or purpose of the curable composition. Although the compound is one kind, there are compounds that fall into two or more categories in the categories of radical polymerizable compounds having hydrophilic functional groups or structures, polyfunctional radical polymerizable compounds, low-viscosity radical polymerizable compounds, compounds that undergo thermal addition reactions or thermal condensation reactions with active hydrogen groups, and resins having hydrophilic functional groups or structures, and it is also preferable to include one or more kinds of such compounds.
[0035] (Water-resistant polyvalent metal ions) The above curable composition contains a water-resistant polyvalent metal ion, which can form a polycoordination state with the anion contained in the curable composition, or can interact with a hydrophilic cation, or can promote a thermal addition reaction or a thermal condensation reaction with an active hydrogen group when such a compound is used, thereby further improving the water resistance of the cured product.
[0036] Preferred examples of the water-resistant polyvalent metal ion include ions of metals or metal oxides belonging to typical metal elements, Group 3 elements of the periodic table, and Group 4 elements of the periodic table. Taking into consideration availability and biological safety, metal or metal oxide ions of zirconium, zirconium oxide, zinc, and aluminum are preferred, and zinc ion is more preferred.
[0037] The curable composition may contain one or more of the water-resistant polyvalent metal ions. When the curable composition contains the water-resistant polyvalent metal ion, the content thereof is preferably 1 to 35 mass%, more preferably 1.5 to 30 mass%, and even more preferably 2 to 25 mass%, relative to 100 mass% of the curable composition.
[0038] (Radical polymerizable compounds having hydrophilic functional groups or structures) By including a radical polymerizable compound having a hydrophilic functional group or structure in the curable composition, the curable composition can have an intermolecular interaction with the cations contained in the curable composition, or when a compound that undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group is used, the reaction can be promoted, thereby further improving the water resistance and hydrophilicity of the cured product.
[0039] The radically polymerizable compound having a hydrophilic functional group or structure has a hydrophilic functional group or structure, and also has a radically polymerizable group. The radical polymerizable compound may have only one type of hydrophilic functional group or structure in the same molecule, or may have two or more types. Also, it may have only one type in the same molecule, or may have two or more types. Similarly, it may have only one type of radical polymerizable group in the same molecule, or may have two or more types. Also, it may have only one type in the same molecule, or may have two or more types.
[0040] Preferred examples of the hydrophilic functional group or structure include a hydroxyl group, a polyoxyethylene structure, an amino group, an amide group, a carboxyl group, a sulfonic acid group, a phosphate group, a quaternary ammonium salt structure, and a betaine structure.
[0041] The radical polymerizable group is preferably a carbon-carbon double bond adjacent to a functional group that activates the carbon-carbon double bond, and the functional group that activates the carbon-carbon double bond is preferably a carbonyl group, an amide group, a cyano group, an aromatic ring, an alkoxy group, an acyloxy group, a carbon-carbon double bond, a halogen, etc., and may be adjacent to only one carbon-carbon double bond, or may be adjacent to two or more types.Preferably, the compound having such a radical polymerizable group is a compound having a (meth)acryloyl group, N-vinyl amides, aromatic vinyls, vinyl ethers, and vinyl esters.
[0042] Specific examples of the radically polymerizable compound having a hydroxyl group include monofunctional (meth)acrylates having only one radically polymerizable group in the same molecule, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol mono(meth)acrylate; polyfunctional (meth)acrylates of polyhydric alcohols, such as glycerol di(meth)acrylate and pentaerythritol tri(meth)acrylate; and epoxy (meth)acrylates obtained by adding (meth)acrylic acid to an epoxy resin.
[0043] Specific examples of radically polymerizable compounds having a polyoxyethylene structure include mono- or di(meth)acrylates of polyalkylene glycols having an oxyethylene structure as a repeating unit, such as polyethylene glycol mono(meth)acrylate, polyethylene glycol di(meth)acrylate, (methoxy)polyethylene glycol (meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate; and ethylene oxide-modified polyfunctional (meth)acrylates obtained by adding (meth)acrylic acid to a compound obtained by adding ethylene oxide to a polyhydric alcohol, such as trimethylolpropane, dipentaerythritol, polyglycerin, or bisphenol A.
[0044] Specific examples of radically polymerizable compounds having an amino group include dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-aminoethyl (meth)acrylate hydrochloride, diallylamine, diallylamine hydrochloride, N-[3-(dimethylamino)propyl]acrylamide, etc. The amino group may be in the form of an amine salt structure with an inorganic or organic acid, as exemplified above.
[0045] Specific examples of the radically polymerizable compound having an amide group include (meth)acrylamide, N,N-dimethylacrylamide, N-(2-hydroxyethyl)acrylamide, acryloylmorpholine, N-vinylcaprolactam, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, and 1,3,5-tri(meth)acryloylhexahydro-1,3,5-triazine.
[0046] Specific examples of radically polymerizable compounds having a carboxy group include (meth)acrylic acid, (meth)acrylic acid esters having carboxyl ends (2-carboxyethyl acrylate, 2-(meth)acryloyloxyethyl succinate, etc.), 2-(meth)allyloxymethyl acrylic acid, itaconic acid, maleic acid, fumaric acid, etc. The carboxy group may be in the form of a carboxylate structure with an inorganic or organic base, such as sodium acrylate, or in the form of a carboxylic acid anhydride structure, such as maleic anhydride.
[0047] Specific examples of radically polymerizable compounds having a sulfonic acid group include 2-acrylamido-2-methylpropanesulfonic acid, vinylsulfonic acid, 2-sulfoethyl(meth)acrylate, sodium p-styrenesulfonate, potassium 3-sulfopropyl(meth)acrylate, etc. The sulfonic acid group may be in the form of a sulfonate salt structure with an inorganic or organic base.
[0048] Specific examples of the radical polymerizable compound having a phosphoric acid group include 2-(meth)acryloyloxyethyl acid phosphate, vinylphosphonic acid, etc. The phosphoric acid group may be in the form of a phosphate structure with an inorganic or organic base.
[0049] Specific examples of the radical polymerizable compound having a quaternary ammonium salt structure include, for example, [2-((meth)acryloyloxy)ethyl]trimethylammonium chloride, [2-((meth)acryloyloxy)ethyl]dimethylbenzylammonium chloride, and (3-acrylamidopropyl)trimethylammonium chloride.
[0050] Specific examples of the radical polymerizable compound having a betaine structure include 2-[[2-((meth)acryloyloxy)ethyl]dimethylammonio]acetic acid, 2-(meth)acryloyloxyethyl phosphorylcholine, 3-[[2-((meth)acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[(3-(meth)acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, bis[2-(methacryloyloxy)ethyl](methyl)ammonio]propane-1-sulfonic acid, and the like.
[0051] The curable composition may contain one or more of the radically polymerizable compounds having the hydrophilic functional groups or structures.
[0052] When the curable composition contains the radical polymerizable compound having the hydrophilic functional group or structure, the content thereof is preferably 1 to 50 mass %, more preferably 3 to 45 mass %, and further preferably 5 to 40 mass %, in 100 mass % of the curable composition.
[0053] (Polyfunctional radical polymerizable compound) By further containing a polyfunctional radically polymerizable compound, the curable composition can introduce covalent crosslinks into the cured product, thereby further improving the water resistance of the cured product and improving mechanical properties such as hardness.
[0054] The polyfunctional radically polymerizable compound may have two or more radically polymerizable groups in one molecule, and may have only one type or two or more types in one molecule.
[0055] The structure of the radically polymerizable group is preferably a carbon-carbon double bond adjacent to a functional group that activates the carbon-carbon double bond.
[0056] Preferred examples of the functional group that activates the carbon-carbon double bond include a carbonyl group, an amide group, a cyano group, an aromatic ring, an alkoxy group, an acyloxy group, a carbon-carbon double bond, and a halogen. Only one functional group may be adjacent to the carbon-carbon double bond, or two or more types of functional groups may be adjacent to the carbon-carbon double bond.
[0057] Preferred examples of the compound having a radically polymerizable group include compounds having a (meth)acryloyl group, N-vinyl amides, aromatic vinyls, vinyl ethers, and vinyl esters.
[0058] Examples of the polyfunctional radically polymerizable compound include polyfunctional (meth)acrylic compounds such as polyfunctional (meth)acrylic esters, vinyl ether group-containing (meth)acrylic esters, allyl group-containing (meth)acrylic esters, polyfunctional (meth)acryloyl group-containing isocyanurates, and polyfunctional urethane (meth)acrylates; polyfunctional 2-(meth)allyloxymethyl acrylic esters; polyfunctional maleimide compounds; polyfunctional vinyl ethers; polyfunctional allyl compounds; and polyfunctional aromatic vinyls.
[0059] Examples of polyfunctional (meth)acrylic acid esters include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, bisphenol A alkylene oxide di(meth)acrylate, and bisphenol F. Examples of the polyfunctional (meth)acrylic acid esters include those described in JP-A-2014-40585, such as alkylene oxide di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ethylene oxide-added trimethylolpropane tri(meth)acrylate.
[0060] Examples of vinyl ether group-containing (meth)acrylic acid esters include the vinyl ether group-containing (meth)acrylic acid esters described in JP 2014-40585 A, such as 2-vinyloxyethyl (meth)acrylate, 3-vinyloxypropyl (meth)acrylate, 1-methyl-2-vinyloxyethyl (meth)acrylate, 2-vinyloxypropyl (meth)acrylate, 4-vinyloxybutyl (meth)acrylate, and 4-vinyloxycyclohexyl (meth)acrylate.
[0061] An example of an allyl group-containing (meth)acrylic acid ester is allyl (meth)acrylate.
[0062] Examples of polyfunctional (meth)acryloyl group-containing isocyanurates include tri(acryloyloxyethyl)isocyanurate, tri(methacryloyloxyethyl)isocyanurate, alkylene oxide-added tri(acryloyloxyethyl)isocyanurate, and alkylene oxide-added tri(methacryloyloxyethyl)isocyanurate.
[0063] Examples of the polyfunctional urethane (meth)acrylate include polyfunctional urethane (meth)acrylates obtained by reacting a polyfunctional isocyanate such as tolylene diisocyanate, isophorone diisocyanate, or xylylene diisocyanate with a hydroxyl group-containing (meth)acrylic acid ester such as 2-hydroxyethyl (meth)acrylate or 2-hydroxypropyl (meth)acrylate.
[0064] Examples of polyfunctional 2-(meth)allyloxymethyl acrylic acid esters include the polyfunctional 2-(meth)allyloxymethyl acrylic acid esters described in Japanese Patent No. 5689628.
[0065] Examples of polyfunctional maleimide compounds include 4,4'-diphenylmethane bismaleimide, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, and phenylmethane maleimide oligomers.
[0066] Examples of polyfunctional vinyl ethers include the polyfunctional vinyl ethers described in JP2014-40585A, such as ethylene glycol divinyl ether, diethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, butylene glycol divinyl ether, hexanediol divinyl ether, bisphenol A alkylene oxide divinyl ether, bisphenol F alkylene oxide divinyl ether, and trimethylolpropane trivinyl ether.
[0067] Examples of polyfunctional allyl compounds include polyfunctional allyl compounds described in JP2014-40585A, such as ethylene glycol diallyl ether, diethylene glycol diallyl ether, polyethylene glycol diallyl ether, propylene glycol diallyl ether, butylene glycol diallyl ether, hexanediol diallyl ether, bisphenol A alkylene oxide diallyl ether, bisphenol F alkylene oxide diallyl ether, and trimethylolpropane triallyl ether.
[0068] An example of the polyfunctional aromatic vinyl is divinylbenzene.
[0069] The polyfunctional radical polymerizable compound may be an oligomer or polymer having a repeating unit based on a monomer as a backbone portion other than the radical polymerizable group. In general, when the molecular weight of a polyfunctional radical polymerizable compound is less than 1000, it is classified as an oligomer, and when the molecular weight is 1000 or more, it is classified as a polymer.
[0070] Examples of the skeleton of the oligomer or polymer of the polyfunctional radical polymerizable compound include a polyester skeleton, a polyether skeleton, a polyurethane skeleton, a conjugated diene polymer skeleton such as polybutadiene or polyisoprene, a poly(meth)acrylate skeleton, a phenol resin skeleton, an aniline resin skeleton, a polyolefin skeleton, a polyamide skeleton, a cycloolefin polymer skeleton, and a polysiloxane skeleton. Among these skeletons, a polyester skeleton, a polyether skeleton, a polyurethane skeleton, a conjugated diene polymer skeleton, a poly(meth)acrylate skeleton, a phenol resin skeleton, and an aniline resin skeleton are preferred. The skeleton portion and the radical polymerizable group may be bonded by a covalent bond, but are preferably bonded via an ester bond and / or a urethane bond.
[0071] Examples of oligomers or polymers of polyfunctional radical polymerizable compounds include urethane (meth)acrylate-based polymerizable oligomers in which a (meth)acryloyl group is bonded to a backbone portion via a urethane bond, urethane (meth)acrylate-based polymers in which a (meth)acryloyl group is bonded to a backbone portion via a urethane bond, epoxy (meth)acrylate-based polymerizable oligomers having a structure in which (meth)acrylic acid is added to an epoxy resin (oligomer or polymer having an epoxy group), and epoxy (meth)acrylate-based polymers having a structure in which (meth)acrylic acid is added to an epoxy resin (oligomer or polymer having an epoxy group). mers, polyester (meth)acrylate-based polymerizable oligomers in which a (meth)acryloyl group is bonded to a polyester skeleton via an ester bond, phenylmethane (meth)acrylate-based polymerizable oligomers in which a (meth)acryloyl group is bonded to a phenol resin skeleton via an ester bond, phenylmethane (meth)acrylate-based polymers in which a (meth)acryloyl group is bonded to a phenol resin skeleton via an ester bond, phenylmethane maleimide-based polymerizable oligomers in which a maleimide group is bonded directly to an aniline resin skeleton, and phenylmethane maleimide-based polymers in which a maleimide group is bonded directly to an aniline resin skeleton.
[0072] The curable composition may contain one or more of the polyfunctional radically polymerizable compounds. When the curable composition contains the polyfunctional radically polymerizable compound, the content thereof is preferably 3 to 50 mass%, more preferably 5 to 45 mass%, and further preferably 7 to 40 mass%, in 100 mass% of the curable composition.
[0073] (Low viscosity radical polymerizable compound) By including a low-viscosity radically polymerizable compound in the curable composition, the viscosity of the curable composition can be reduced to improve reaction efficiency, or the content of a high-viscosity substance can be adjusted to improve water resistance.
[0074] The low-viscosity radically polymerizable compound preferably has a viscosity at 23° C. of 180 mPa·s or less, more preferably 140 mPa·s or less, and even more preferably 100 mPa·s or less.
[0075] The low-viscosity radically polymerizable compound may have only one type of radically polymerizable group in the same molecule, or may have two or more types of radically polymerizable groups in the same molecule. Also, the compound may have only one type of radically polymerizable group in the same molecule, or may have two or more types of radically polymerizable groups in the same molecule.
[0076] The radical polymerizable group may be the same as the radical polymerizable group in the radical polymerizable compound having the above-mentioned hydrophilic functional group or structure. As the low-viscosity radical polymerizable compound, from the viewpoints of availability, radical polymerizability, dilutability, etc., monofunctional (meth)acrylic acid esters and monofunctional 2-(meth)allyloxymethylacrylic acid esters are particularly preferred.
[0077] Examples of monofunctional (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, sec-amyl (meth)acrylate, tert-amyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and silyl (meth)acrylate. Examples of the acrylates include cyclohexyl, cyclohexylmethyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate.
[0078] Examples of monofunctional 2-(meth)allyloxymethyl acrylates include methyl 2-(meth)allyloxymethyl acrylate, ethyl 2-(meth)allyloxymethyl acrylate, n-propyl 2-(meth)allyloxymethyl acrylate, isopropyl 2-(meth)allyloxymethyl acrylate, n-butyl 2-(meth)allyloxymethyl acrylate, sec-butyl 2-(meth)allyloxymethyl acrylate, tert-butyl 2-(meth)allyloxymethyl acrylate, n-amyl 2-(meth)allyloxymethyl acrylate, sec-amyl 2-(meth)allyloxymethyl acrylate, tert-amyl 2-(meth)allyloxymethyl acrylate, n-hexyl 2-(meth)allyloxymethyl acrylate, 2-ethylhexyl 2-(meth)allyloxymethyl acrylate, ... p) cyclohexyl allyloxymethylacrylate, cyclohexylmethyl 2-(meth)allyloxymethylacrylate, octyl 2-(meth)allyloxymethylacrylate, lauryl 2-(meth)allyloxymethylacrylate, benzyl 2-(meth)allyloxymethylacrylate, isobornyl 2-(meth)allyloxymethylacrylate, tricyclodecanyl 2-(meth)allyloxymethylacrylate, 2-methoxyethyl 2-(meth)allyloxymethylacrylate, 2-ethoxyethyl 2-(meth)allyloxymethylacrylate, phenoxyethyl 2-(meth)allyloxymethylacrylate, tetrahydrofurfuryl 2-(meth)allyloxymethylacrylate, and (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl 2-(meth)allyloxymethylacrylate.
[0079] The curable composition may contain one or more of the low viscosity radically polymerizable compounds. When the curable composition contains the low-viscosity radically polymerizable compound, the content thereof is preferably 3 to 40 mass%, more preferably 5 to 35 mass%, and further preferably 7 to 30 mass%, based on 100 mass% of the curable composition.
[0080] (Compounds that undergo thermal addition or condensation reactions with active hydrogen groups) The curable composition further contains a compound that undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group, thereby introducing covalent crosslinking into the cured product, thereby improving the water resistance, hardness, and other mechanical properties of the cured product.
[0081] The functional group possessed by the compound which undergoes a thermal addition reaction or thermal condensation reaction with the active hydrogen group may be any functional group which undergoes a thermal addition reaction or thermal condensation reaction with the active hydrogen group, and may have only one type or two or more types in the same molecule. Also, it may have only one type or two or more types in the same molecule.
[0082] Examples of functional groups that undergo a thermal addition reaction or thermal condensation reaction with an active hydrogen group include an epoxy group, an oxetanyl group, a carbodiimide group, an oxazoline group, an isocyanate group, an alkoxysilyl group, and a hydroxymethyl group or alkoxymethyl group bonded to a nitrogen atom. The compound having a functional group which undergoes a thermal addition reaction or thermal condensation reaction with an active hydrogen group may be a low molecular weight compound, an oligomer, or a high molecular weight compound.
[0083] Specific examples of the compound having an epoxy group include glycidyl (meth)acrylate, 2-ethylhexyl glycidyl ether, p-tert-butylphenyl glycidyl ether, N-glycidyl phthalimide, methoxypolyethylene glycol monoglycidyl ether, lauryloxypolyethylene glycol monoglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, lauryloxypolyethylene glycol glycidyl ether, bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, sorbitol polyglycidyl ether, Compounds having a glycidyl group, such as diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, phenol novolac type polyglycidyl ether, o-cresol novolac type polyglycidyl ether, triglycidyl isocyanurate, 4,4'-methylenebis(N,N-diglycidylaniline), 3-glycidyloxypropyltrimethoxysilane, radical (co)polymers of compounds having a radical polymerizable group and a glycidyl group (glycidyl (meth)acrylate, etc.); (3,4-epoxy Examples of the compound include compounds having an alicyclic epoxy group, such as bis(3,4-epoxycyclohexyl)methyl(meth)acrylate, (3,4-epoxycyclohexylmethyl)3,4-epoxycyclohexanecarboxylate, 1,2-epoxy-4-vinyl-1-cyclohexene, bis(3,4-epoxycyclohexylmethyl)adipate, 4-vinylcyclohexene dioxide, and radical (co)polymers of compounds having a radical polymerizable group and an alicyclic epoxy group (e.g., (3,4-epoxycyclohexyl)methyl(meth)acrylate). Among these, compounds having a glycidyl group are preferred from the viewpoint of reactivity.
[0084] Examples of compounds having an oxetanyl group include low molecular weight compounds such as (3-ethyl-3-oxetanyl)methyl (meth)acrylate, 3-allyloxymethyl-3-ethyloxetane, 2-ethylhexylmethyl-3-ethyloxetane, bis(3-ethyl-3-oxetanylmethyl)ether, bis[(3-ethyl-3-oxetanyl)methyl]isophthalate, and 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl; and radical (co)polymers of compounds having an oxetanyl group and a radical polymerizable group such as (3-ethyl-3-oxetanyl)methyl (meth)acrylate.
[0085] Examples of compounds having a carbodiimide group include N,N'-diisopropylcarbodiimide, N,N'-di-tert-butylcarbodiimide, N,N'-dicyclohexylcarbodiimide, bis(2,6-diisopropylphenyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and Carbodista (product name, Teijin Limited).
[0086] Examples of compounds having an oxazoline group include Epocross WS-300 (product name, Nippon Shokubai Co., Ltd.), Epocross WS-500 (product name, Nippon Shokubai Co., Ltd.), Epocross WS-700 (product name, Nippon Shokubai Co., Ltd.), and Epocross RPS-1005 (product name, Nippon Shokubai Co., Ltd.).
[0087] Examples of compounds having an isocyanate group include low molecular weight compounds such as 2-isocyanatoethyl (meth)acrylate, tolylene diisocyanate, xylylene diisocyanate, bis(isocyanatomethyl)cyclohexane, hexamethylene diisocyanate, isophorone diisocyanate, and diphenylmethane diisocyanate (monomeric MDI); polymeric MDI, radical (co)polymers of compounds having a radical polymerizable group and an isocyanate group such as 2-isocyanatoethyl (meth)acrylate, and polymeric compounds such as isocyanate group-terminated prepolymers obtained by reacting a polyol with an excess of polyisocyanate; and the like. The isocyanate group may be an isocyanate group masked with a blocking agent such as phenol, ε-caprolactam, methyl ethyl ketone oxime, diethyl malonate, ethyl acetoacetate, or dimethylpyrazole.
[0088] Examples of the compound having an alkoxysilyl group include tetramethoxysilane, tetraethoxysilane, hydrolysis / polycondensation oligomer of tetramethoxysilane, hydrolysis / polycondensation oligomer of tetraethoxysilane, 3-(trimethoxysilyl)propyl(meth)acrylate, 3-[dimethoxy(methyl)silyl]propyl(meth)acrylate, 3-(triethoxysilyl)propyl(meth)acrylate, 3-[diethoxy(methyl)silyl]propyl(meth)acrylate, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 3-glycidyloxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxy ... Examples of suitable low molecular weight compounds include silane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, vinyltrimethoxysilane, vinyltriethoxysilane, tris[3-(trimethoxysilyl)propyl] isocyanurate, bis[3-(trimethoxysilyl)propyl]amine, and 1,6-bis(trimethoxysilyl)hexane; and polymer compounds such as radical (co)polymers of compounds having a radical polymerizable group and an alkoxysilyl group, such as terminal alkoxysilyl-type polydimethylsiloxane, 3-(trimethoxysilyl)propyl(meth)acrylate, and 3-(triethoxysilyl)propyl(meth)acrylate.
[0089] Examples of compounds having a hydroxymethyl group or an alkoxymethyl group bonded to a nitrogen atom include hydroxymethylated (meth)acrylamide compounds such as N-(hydroxymethyl)(meth)acrylamide, N-(methoxymethyl)(meth)acrylamide, radical (co)polymers of N-(hydroxymethyl)(meth)acrylamide, and N-(methoxymethyl)(meth)acrylamide; melamine resins such as hexamethylol melamine, partial or complete methyl etherification products of hexamethylol melamine, partially methylolated melamine, and methyl etherification products of partially methylolated melamine; benzoguanamine resins such as tetramethylol benzoguanamine and methyl etherification products of tetramethylol benzoguanamine; urea resins such as 1,3,4,6-tetrakis(methoxymethyl)glycoluril, dimethylol dihydroxyethylene urea, and methyl etherification products of dimethylol dihydroxyethylene urea; and the like.
[0090] The curable composition may contain one or more compounds that undergo a thermal addition reaction or a thermal condensation reaction with the active hydrogen group. Among the compounds that undergo thermal addition reaction or thermal condensation reaction with the active hydrogen group, from the viewpoints of improving water resistance, resistance to thermal discoloration, and storage stability, compounds having an epoxy group and compounds having an alkoxysilyl group are preferred, and it is more preferred to include both a compound having an epoxy group and a compound having an alkoxysilyl group.It is also preferred to include a compound having an epoxy group and a compound having an alkoxysilyl group.
[0091] When the curable composition contains a compound that undergoes a thermal addition reaction or a thermal condensation reaction with the active hydrogen group, the content thereof is preferably 3 to 70 mass %, more preferably 5 to 40 mass %, even more preferably 7 to 35 mass %, and even more preferably 7 to 30 mass %, relative to 100 mass % of the curable composition.
[0092] (Resin with hydrophilic functional groups or structures) The curable composition further contains a resin having a hydrophilic functional group or structure, and thereby the resin can undergo intermolecular interactions with ions contained in the curable composition, or, in the case of using a compound that undergoes a thermal addition reaction or a thermal condensation reaction with an active hydrogen group, can react with such a compound, thereby further improving the water resistance of the cured product.
[0093] Examples of hydrophilic functional groups or structures include hydroxyl groups, polyoxyethylene structures, amino groups (which may be amine salt structures with inorganic or organic acids), amide groups, carboxy groups (which may be carboxylate structures with inorganic or organic bases), sulfonic acid groups (which may be sulfonate structures with inorganic or organic bases), phosphoric acid groups (which may be phosphate structures with inorganic or organic bases), quaternary ammonium salt structures, and betaine structures.These functional groups and structures include the same as those described in the radical polymerizable compounds having the above-mentioned hydrophilic functional groups or structures.
[0094] Specific examples of resins having the above-mentioned hydrophilic functional groups or structures include polyvinyl alcohol, 2-hydroxyethyl acrylate (co)polymer, polyethylene glycol, poly(ethylene glycol-propylene glycol) copolymer, polyethylene ion, poly(diallyldimethylammonium chloride), polyvinylpyrrolidone, sodium polyacrylate, etc.
[0095] The curable composition may contain one or more of the above resins having hydrophilic functional groups or structures. When the curable composition contains the resin having the hydrophilic functional group or structure, the content thereof is preferably 3 to 30 mass %, more preferably 4 to 25 mass %, and further preferably 5 to 20 mass %, in 100 mass % of the curable composition.
[0096] [Surfactants] The curable composition preferably further contains a surfactant. When the curable composition contains one or more surfactants, the hydrophilicity of the cured product and the leveling property of the curable composition can be improved.
[0097] The surfactant is not particularly limited as long as it is a compound having a hydrophilic portion and a lipophilic portion in the same molecule and is a commonly known compound as a surfactant, and examples of the surfactant include known anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants.
[0098] Specific examples of the anionic surfactant include fatty acid salts such as fatty acid alkali metal salts, such as sodium oleate and potassium oleate; higher alcohol sulfates, such as sodium lauryl sulfate and ammonium lauryl sulfate; alkylbenzenesulfonates and alkylnaphthalenesulfonates, such as sodium dodecylbenzenesulfonate and sodium alkylnaphthalenesulfonate; polyoxyethylene sulfate salts, such as naphthalenesulfonate-formaldehyde condensates, dialkylsulfosuccinates, dialkylphosphate salts, and sodium polyoxyethylene alkylphenyl ether sulfate; and fluorine-containing anionic surfactants, such as perfluoroalkylcarboxylates, perfluoroalkylsulfonates, and perfluoroalkylphosphate esters.
[0099] Specific examples of cationic surfactants include amine salts such as laurylamine acetate, triethanolamine monoformate, and stearamidoethyl diethylamine acetate; alkyltrimethylammonium salts such as lauryltrimethylammonium chloride and stearyltrimethylammonium chloride; dialkyldimethylammonium salts such as dilauryldimethylammonium chloride, distearyldimethylammonium chloride, lauryldimethylbenzylammonium chloride, and stearyldimethylbenzylammonium chloride; and fluorine-containing cationic surfactants such as perfluoroalkyltrimethylammonium salts and perfluoroalkenyltrimethylammonium salts.
[0100] Specific examples of nonionic surfactants include polyoxyethylene higher alcohol ethers such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether; polyoxyethylene alkylaryl ethers such as polyoxyethylene octylphenol and polyoxyethylene nonylphenol; polyoxyethylene sorbitan fatty acid esters such as polypropylene glycol ethylene oxide adducts, polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate; phosphate esters such as alkyl phosphate esters and polyoxyethylene alkyl ether phosphate esters; sugar esters, cellulose ethers; and perfluoroalkylamine oxalates. fluorine-containing nonionic surfactants such as perfluoroalkenylamine oxides, perfluoroalkylethylene oxide adducts, perfluoroalkenylethylene oxide adducts, oligomers having a perfluoroalkyl group and a hydrophilic group, oligomers having a perfluoroalkenyl group and a hydrophilic group, oligomers having a perfluoroalkyl group and a lipophilic group, oligomers having a perfluoroalkenyl group and a lipophilic group, oligomers having a perfluoroalkyl group, a hydrophilic group and a lipophilic group, oligomers having a perfluoroalkenyl group, a hydrophilic group and a lipophilic group, and oligomers having a perfluoroalkenyl group, a hydrophilic group and a lipophilic group; modified silicone-based nonionic surfactants such as polyester-modified silicone and polyether-modified silicone, and the like.
[0101] Specific examples of amphoteric surfactants include fatty acid type amphoteric surfactants such as dimethylalkyl lauryl betaine, dimethylalkyl stearyl betaine, lauryl dimethylaminoacetate betaine, and lauric acid amidopropyl dimethylaminoacetate betaine; sulfonic acid type amphoteric surfactants such as dimethylalkyl sulfobetaine; and alkyl glycines.
[0102] The surfactant may have a radical polymerizable group, or a functional group that undergoes a thermal addition reaction or thermal condensation reaction with an active hydrogen group. As the type of radical polymerizable group, from the viewpoint of polymerizability, a carbon-carbon double bond adjacent to the functional group that activates the carbon-carbon double bond is preferable, but considering availability as a surfactant, a surfactant having a (meth)acryloyl group, a surfactant having an allyloxy structure, and a surfactant having an aromatic vinyl structure are preferable. As the type of functional group that undergoes a thermal addition reaction or thermal condensation reaction with an active hydrogen group, the above-mentioned epoxy group, oxetanyl group, carbodiimide group, aziridine group, isocyanate group, alkoxysilyl group, hydroxymethyl group or alkoxymethyl group bonded to a nitrogen atom, etc. are mentioned, but considering availability as a surfactant, a surfactant having an epoxy group and a surfactant having an alkoxysilyl group are preferable.
[0103] The content of the surfactant may be adjusted depending on the application or purpose, and it does not have to be included; however, when used, the content is preferably 0.001 to 20 mass%, more preferably 0.003 to 15 mass%, and even more preferably 0.005 to 10 mass%, relative to 100 mass% of the curable composition.
[0104] [Other ingredients] The curable composition may further contain inorganic fine particles, a radical polymerization initiator, a radical polymerization inhibitor, a solvent, and the like, in addition to the above-mentioned components.
[0105] (Inorganic fine particles) The curable composition contains one or more types of inorganic fine particles, which can improve the hydrophilicity and hardness of the cured product.
[0106] Examples of inorganic fine particles include fine particles of silica, alumina, zinc oxide, tin oxide, iron oxide, titanium oxide, indium oxide, zirconium oxide, vanadium oxide, cerium oxide, antimony oxide, indium-doped tin oxide, etc. Among these inorganic fine particles, silica, alumina, zinc oxide, titanium oxide, and zirconium oxide are more preferable from the viewpoint of maintaining high transparency.
[0107] The inorganic fine particles may be surface-modified, for example, may have a lipophilic alkyl group or a radical polymerizable group on the surface. From the viewpoint of transparency, the particle size of the inorganic fine particles is preferably from 1 to 100 nm, more preferably from 1 to 50 nm, and even more preferably from 1 to 30 nm.
[0108] The content of inorganic fine particles may be adjusted according to the application or purpose, and may not be included; however, when used, the content is preferably 0.1 to 90 mass%, more preferably 0.5 to 70 mass%, and even more preferably 1 to 60 mass%, relative to 100 mass% of the curable composition.
[0109] (Radical polymerization initiator) The curable composition can have improved radical polymerizability by containing one or more radical polymerization initiators.
[0110] Radical polymerization initiators can be classified into photoradical initiators that generate radicals upon irradiation with active energy rays and thermal radical initiators that generate radicals upon heating. They can be selected according to the application or purpose, and photoradical initiators and thermal radical initiators may be used in combination.
[0111] Examples of photoradical initiators include alkylphenone compounds, benzophenone compounds, benzoin compounds, ketal compounds, anthraquinone compounds, phosphine oxide compounds, thioxanthone compounds, halomethylated triazine compounds, halomethylated oxadiazole compounds, biimidazole compounds, oxime ester compounds, titanocene compounds, benzoic acid ester compounds, acridine compounds, etc., but the present disclosure is not limited to these examples. These photoradical initiators may be used alone or in combination of two or more.
[0112] Specific examples of the compounds include acetophenone, 1,1-dichloroacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzene} alkylphenone compounds such as 2-methyl-1-(4-morpholinophenyl)-2-propan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone; benzophenone, 4,4'-bis(dimethylamino)benzophenone, 2-carboxybenzophenone, 4-benzoyl-4'-methyldiphenyl benzoin compounds such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; ketal compounds such as acetophenone dimethyl ketal and benzyl dimethyl ketal; anthraquinone compounds such as 2-ethylanthraquinone, 2-t-butylanthraquinone, 2-chloroanthraquinone, and 2-amylanthraquinone; 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,6-dimethoxyphenyl)- ... phosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and [3-(3,4-dimethyl-9-oxothioxanthen-2-yl)oxy-2-hydroxypropyl]-trimethylazanium chloride;Halomethylated triazine compounds such as 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-sec-triazine, 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-sec-triazine, 2-(4-ethoxynaphthyl)-4,6-bis(trichloromethyl)-sec-triazine, and 2-(4-ethoxycarbonylnaphthyl)-4,6-bis(trichloromethyl)-sec-triazine; 2-trichloromethyl-5-[β-(2'-benzofuryl) halomethylated oxadiazole compounds such as 2-trichloromethyl-5-[β-(2'-(6''-benzofuryl)vinyl)]-1,3,4-oxadiazole, 2-trichloromethyl-5-furyl-1,3,4-oxadiazole; 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2 Biimidazole compounds such as 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole; oxime ester compounds such as 1-[4-(phenylthio)-,2-(O-benzoyloxime)]-1,2-octanedione, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-,1-(O-acetyloxime)ethanone; bis(η5-2,4-cyclopentadiene-1 titanocene compounds such as bis(2,4,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium; acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; benzoic acid ester compounds such as p-dimethylaminobenzoic acid and p-diethylaminobenzoic acid; and acridine compounds such as 9-phenylacridine.
[0113] As the thermal radical initiator, an organic peroxide initiator or an azo initiator is suitable. For example, organic peroxide initiators such as methyl ethyl ketone peroxide, cyclohexanone peroxide, methylcyclohexanone peroxide, methyl acetoacetate peroxide, and acetyl acetate peroxide, and azo initiators such as 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, 1-[(1-cyano-1-methylethyl)azo]formamide, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobisisobutyronitrile, etc., are described in JP-A-2020-122053. Examples of such organic peroxide initiators and azo initiators include the organic peroxide initiators and azo initiators described in JP-A-2020-122053.
[0114] The content of the radical polymerization initiator may be adjusted depending on the application or purpose, and it does not have to be included; however, when used, the content is preferably 0.01 to 10 mass %, more preferably 0.05 to 8 mass %, and even more preferably 0.01 to 7 mass %, relative to 100 mass % of the curable composition of the present invention.
[0115] (Radical polymerization inhibitor) The curable composition contains one or more radical polymerization inhibitors, which makes it possible to inhibit undesired radical polymerization during storage, transportation, and various operations in the preparation and processing of the composition.
[0116] As the radical polymerization inhibitor, a primary antioxidant having a radical chain inhibitory property and / or a secondary antioxidant having a peroxide decomposition property can be used.
[0117] Examples of the primary antioxidant include hydroquinones, benzoquinones, phenols, aromatic amines, phenothiazines, metal dithiocarbamate salts, and nitroso compounds. Examples of the secondary antioxidant include phosphorus compounds such as phosphine and phosphite, and sulfur compounds such as thioether, mercaptobenzimidazole, and thiourea. The primary antioxidant and the secondary antioxidant may be used alone, but it is more preferable to use them in combination. Among primary antioxidants, phenols are preferred from the viewpoint of inhibiting coloration, and among secondary antioxidants, thioethers are preferred from the viewpoint of acid resistance and hydrolysis resistance.
[0118] Examples of phenols include monoetherified hydroquinones, hindered phenols and their polymers (including dimers) or derivatives of the polymers, and semi-hindered phenols and their polymers (including dimers) or derivatives of the polymers.
[0119] Examples of monoetherified hydroquinones include hydroquinone monomethyl ether and hydroquinone mono-n-butyl ether, as described in JP-A-2014-40585.
[0120] Examples of the hindered phenols include 2,6-bis(tert-butyl)-4-methylphenol, octadecyl-3-(3,5-ditert-butyl-4-hydroxyphenyl)propionate, and isooctyl-3-(3,5-ditert-butyl-4-hydroxyphenyl)propionate, and the hindered phenols described in JP-A-2014-40585. Examples of the oligomers or oligomer derivatives of hindered phenols include the compounds described in JP-A-2014-40585.
[0121] Examples of the semi-hindered phenols include those described in JP-A-2014-40585, such as 6-tert-butyl-o-cresol and 6-tert-butyl-2,4-xylenol. Examples of the polymerized products or derivatives of the polymerized products of semi-hindered phenols include the compounds described in JP-A-2014-40585.
[0122] Examples of phosphines include those described in JP-A-2014-40585, such as triethylphosphine, tributylphosphine, tris(2-ethylhexyl)phosphine, and triphenylphosphine.
[0123] Examples of the phosphite include diethyl hydrogen phosphite, bis(2-ethylhexyl) hydrogen phosphite, dilauryl hydrogen phosphite, diphenyl hydrogen phosphite, triethyl phosphite, tributyl phosphite, tris(2-ethylhexyl) phosphite, and the phosphites described in JP-A-2014-40585.
[0124] Examples of thioethers include 2,2'-thiodiglycolic acid, (ethylenedithio)diacetic acid, 2,2'-(ethylenedithio)diethanol, 3,3'-thiodipropionic acid, dimethyl 3,3'-thiodipropionate, and 3-laurylthiopropionic acid, as well as thioethers described in JP2014-40585A.
[0125] The content of the radical polymerization inhibitor may be adjusted depending on the application or purpose, and it does not have to be included; however, when used, the content is preferably 0.0005 to 10 mass%, more preferably 0.001 to 5 mass%, and even more preferably 0.002 to 3 mass%, relative to 100 mass% of the curable composition of the present invention.
[0126] (solvent) The curable composition contains one or more solvents, which makes it easier to adjust the viscosity and the thickness of the coating film.
[0127] As the solvent, from the viewpoint of compatibility with the above-mentioned 2-(meth)allyloxymethylacrylic acid ion, hydrophilic cation, and component that improves water resistance, water or a polar organic solvent containing at least one structure selected from the group consisting of a hydroxyl group, an ether structure, an ester structure, a ketone structure, and an amide structure is preferred.
[0128] Specific examples of the polar solvent include monoalcohols such as methanol, ethanol, and isopropanol; glycols such as ethylene glycol and propylene glycol; cyclic ethers such as tetrahydrofuran and dioxane; glycol monoethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and diethylene glycol monomethyl ether; glycol ethers such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, propylene glycol dimethyl ether, and propylene glycol diethyl ether; ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene Examples of the alkyl ester include glycol monoether esters such as glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; alkyl esters such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl lactate, ethyl lactate, butyl lactate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, methyl acetoacetate, and ethyl acetoacetate; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; and amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone.
[0129] The content of the solvent may be adjusted depending on the application or purpose, and may not be included, but when used, the content is preferably 1 to 500 parts by mass, more preferably 2 to 400 parts by mass, and even more preferably 3 to 300 parts by mass, relative to 100 parts by mass of the total non-volatile content of the curable composition of the present invention. Note that the "total non-volatile content" refers to the total amount of components that form a cured product in the curable composition (excluding the solvent and the like that volatilizes during the formation of the cured product).
[0130] The curable composition may further contain components other than those described above depending on the purpose and application of the composition, and examples of such components include light stabilizers, ultraviolet absorbers, antistatic agents, antibacterial agents, antifungal agents, deodorants, thixotropic agents, organic fine particles, dyes, pigments, dispersants, matting agents, antisettling agents, antifoaming agents, flame retardants, and release agents. These may be appropriately selected from known agents. The content of these agents may also be appropriately selected from known methods.
[0131] <Cured product> The cured product of the present invention is obtained by curing the above-mentioned curable composition. The cured product of the present invention is a cured product of the above-mentioned curable composition, and has excellent hydrophilicity and water resistance. Even if the cured product is hydrophilic, if it is water-soluble, it will be easily removed by contact with water or moisture, making it of no practical use, so it is necessary for the cured product to be water-insoluble. In this case, the water-insoluble nature of the product is judged by whether or not the cured product retains its original shape without dissolving or dispersing in water when immersed in pure water at 23°C for one hour. The judgment of whether or not the product retains its original shape is made by visual inspection.
[0132] There are various indices for judging hydrophilicity, such as breath antifogging property, warm water or hot steam antifogging property, water contact angle, surface tension, surface free energy, etc., but breath antifogging property and water contact angle are preferred from the viewpoint of simplicity and reproducibility. It is preferable that the cured product of the present invention satisfies at least one of the following as an index of hydrophilicity. Index (I) Shows anti-fogging properties against exhaled air Indicator (II) Water contact angle is 50° or less
[0133] Indicator(I) The judgment of whether or not anti-fogging properties are exhibited against breath is made by the following method: In an environment of 23°C temperature and 50% humidity, breath is blown onto the surface of the cured product from a position 5 cm away in a vertical direction for 3 seconds, and the surface of the cured product is then visually observed. If no fogging occurs, it is judged to have anti-fogging properties, and if fogging occurs, it is judged not to have anti-fogging properties. The occurrence of cloudiness is judged by visual inspection.
[0134] Indicator (II) The water contact angle of the cured product is measured by determining whether or not the contact angle becomes 50° or less within 3 minutes after a water droplet (2 μL) is placed on the surface of the cured product. For applications requiring antifouling properties, the water contact angle is preferably 40° or less, more preferably 30° or less, and even more preferably 20° or less, particularly for applications classified as superhydrophilic. The water contact angle is measured using a contact angle meter capable of measuring by the droplet method, and 2 μL of water is dropped in an environment at a temperature of 23° C. and a humidity of 50%, and the static contact angle is calculated by the θ / 2 method based on the image of the droplet after the droplet has landed.
[0135] When the occurrence of cloudiness can be easily visually confirmed, it is preferable to judge by index (I), and when the cloudiness is difficult to visually confirm, such as when the cured product is colored or matte, it is preferable to judge by index (II). The above cured product may satisfy only index (I) or index (II), or may satisfy both, depending on the application. Such a water-insoluble cured product of the above-mentioned curable composition, which satisfies at least one of the above index (I) and index (II), also constitutes one aspect of the present invention.
[0136] The method for curing the curable composition is not particularly limited, but a preferred example is a method in which radicals are generated and radical polymerization is carried out.
[0137] The radical generating method includes a method of heating the curable composition and / or a method of irradiating the curable composition with active energy rays. Heating or irradiating the curable composition with active energy rays may be performed in one step or in two or more steps. When both heating and irradiation with active energy rays are carried out, they may be carried out simultaneously or separately. In the case where heating or irradiation with active energy rays is performed, the curable composition preferably contains a radical polymerization initiator.
[0138] The heating temperature for the radical polymerization may be appropriately selected depending on the presence or absence, type, content, and application of a radical polymerization initiator. When a thermal radical initiator is used, the heating temperature is preferably 40 to 160°C, more preferably 50 to 150°C, and even more preferably 60 to 140°C.
[0139] The above-mentioned active energy rays can be those that are commonly used, including electromagnetic waves such as gamma rays, X-rays, ultraviolet rays, visible light rays, and infrared rays, and particle rays such as electron beams, neutron beams, and proton beams. Among these, in terms of energy strength, energy ray generator, and the like, gamma rays, X-rays, ultraviolet rays, visible light rays, and electron beams are preferred, ultraviolet rays, visible light rays, and electron beams are more preferred, and ultraviolet rays are the most preferred. When no photoradical initiator is used, it is preferred to use active energy rays with high energy such as gamma rays, X-rays, and electron beams, and when a photoradical initiator is used, it is preferred to use active energy rays such as ultraviolet rays and visible light rays, which have relatively low energy but are easy to generate and are economical.
[0140] The radical polymerization of the curable composition is preferably carried out under a low oxygen concentration in order to suppress the inhibition of radical polymerization caused by oxygen.To achieve a low oxygen concentration, the following methods can be mentioned: blowing an inert gas such as nitrogen or argon on the surface of the curable composition; placing the curable composition in a sealed container filled with an inert gas; placing the curable composition in a sealed container capable of reducing pressure and reducing the pressure; and adhering a cover film that can be released after curing to the surface of the curable composition.
[0141] The reaction for obtaining the cured product of the present invention includes at least generating radicals in the curable composition and carrying out radical polymerization, but may also include other reactions, and preferred examples of such reactions include thermal addition reaction with active hydrogen groups and thermal condensation reaction with active hydrogen groups. When carrying out these reactions, it is preferred that the curable composition contains a compound that undergoes thermal addition reaction or thermal condensation reaction with the active hydrogen groups. These reactions may be carried out before, simultaneously with, or after radical polymerization.
[0142] The heating temperature in the thermal addition reaction or thermal condensation reaction with the active hydrogen group may be appropriately selected depending on the type, content, and application of the compound that undergoes the thermal addition reaction or thermal condensation reaction with the active hydrogen group, but is preferably 40 to 170°C, more preferably 70 to 160°C, and even more preferably 90 to 150°C.
[0143] <Article Having Cured Material> The present invention also relates to an article having the above-mentioned cured product on its surface. The above-mentioned curable composition for obtaining the cured product is applied to the surface of a substrate, and the cured product is obtained by the above-mentioned method, whereby an article having a cured film with excellent hydrophilicity and water resistance can be obtained.
[0144] The type and shape of the substrate are not particularly limited and may be appropriately selected according to the application and purpose.Specific examples of the substrate include inorganic substrates such as glass, iron, stainless steel, and aluminum; organic substrates such as silicone resin, acrylic resin, methacrylic resin, fluororesin, alkyd resin, aminoalkyd resin, vinyl resin, polyester resin, styrene-butadiene resin, polyolefin resin, polystyrene resin, polyketone resin, polyamide resin, polycarbonate resin, polyacetal resin, polyetheretherketone resin, polyphenylene oxide resin, polysulfone resin, polyphenylenesulfone resin, polyether resin, polyvinyl chloride resin, polyvinylidene chloride resin, urea resin, phenol resin, melamine resin, epoxy resin, urethane resin, silicone-acrylic resin, cellulose-based resin, isoprene-based resin such as natural rubber, and protein-based resin such as casein.
[0145] The surface of the substrate to which the curable composition is applied may be provided with a functional layer such as an adhesion improving primer, a colored coating material, an antireflection layer, a gas barrier layer, or a transparent conductive layer, or may be subjected to a surface treatment such as a corona discharge treatment, a frame treatment, or a plasma treatment.
[0146] The method for applying the curable composition is not particularly limited and may be appropriately selected depending on the type and shape of the substrate. Specific examples of the method include spraying, flow coating, roll coating, brush coating, dip coating, spin coating, screen printing, casting, gravure printing, and flexographic printing.
[0147] After the curable composition is applied, drying or the like is carried out as necessary, and then the above-mentioned curing method is carried out, whereby a hydrophilic cured film can be satisfactorily formed on the substrate.
[0148] The film thickness of the cured product in the above-mentioned article is not particularly limited and may be appropriately selected depending on the purpose or use, but in order to form a smooth and uniform coating film using a general-purpose device, it is preferably 0.5 to 30 μm, more preferably 1 to 20 μm, and even more preferably 2 to 15 μm.
[0149] <Application> Since the cured product of the present invention has excellent hydrophilicity and water resistance, the curable composition, cured product and article of the present invention can be used in a wide range of applications where hydrophilicity and water resistance are required. The curable composition, cured product, and article of the present invention can be used in a variety of applications, ranging from everyday items such as glasses, helmets, bathroom mirrors, automobile lamps, heat exchangers for air conditioners, camera lenses, and endoscopes, to building materials, transportation equipment, home appliances, precision electronic devices, and medical equipment. EXAMPLES
[0150] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0151] The measurement and evaluation methods in the present examples are as follows. <Quantitative determination of 2-allyloxymethylacrylic acid> 2-allyloxymethylacrylic acid with a purity of 96.5% was prepared, containing 0.04% (based on the total amount of the liquid) of hydroquinone monomethyl ether and 0.06% (based on the total amount of the liquid) of 2,2'-(ethylenedithio)diethanol as radical polymerization inhibitors. The purity was measured using the capillary electrophoresis system described below. -Measuring equipment- Capillary electrophoresis system Agilent 7100 (Agilent Technologies, Inc.) -Measurement conditions- The measurement was performed by the indirect absorption method using a background absorbent. Capillary: Bubble self-fused silica capillary (inner diameter 75 μm × total length 80.5 cm) Running solution: Running solution for anion analysis (pH=8.2) Applied voltage: -20kV -Quantitative method- Quantitation was performed by the internal standard method based on the area ratio (internal standard: sodium propionate). Preparation of standard sample: Dissolve sodium propionate and the substance to be quantified (sodium salt of carboxylate ion) in heavy water. 1 The molar ratio was quantified by 1 H-NMR, and then the mixture was diluted with ultrapure water to prepare a standard sample for creating a calibration curve. Preparation of measurement samples: The sodium propionate aqueous solution and the test sample were weighed and diluted with 0.1N sodium hydroxide aqueous solution and ultrapure water to prepare measurement samples.
[0152] <Water resistance> -Making the laminate- For Examples 1 to 11 and Comparative Examples 1 to 6, the curable composition was first applied onto a 100 μm-thick PET film (Lumirror Film T60, Toray Industries, Inc.) using a bar coater No. 4, and then dried for 1 minute on a hot plate heated to 70° C. to obtain an uncured coating film with a dry thickness of about 5 μm. Next, the coating was applied onto a belt conveyor-type UV irradiation device (high-pressure mercury lamp, illuminance 150 mW / cm 2 , nitrogen atmosphere) was used, and the cumulative light dose on the coating surface was 1000 mJ / cm 2 Thus, a laminate in which a cured layer was formed on the PET film was obtained. For Examples 12 to 20, the curable composition was first applied onto a 100 μm-thick PET film (Lumirror Film T60, Toray Industries, Inc.) using a bar coater No. 4 to obtain an uncured coating film having a dry thickness of 8 to 9 μm. Then, the curable composition was applied onto a PET film having a dry thickness of 8 to 9 μm using a belt conveyor type UV irradiation device (high pressure mercury lamp, illuminance 150 mW / cm 2 , nitrogen atmosphere) was used, and the cumulative light dose on the coating surface was 1000 mJ / cm 2The film was fixed to a glass plate with clips and heated in an oven at 130° C. for 30 minutes, and then removed from the oven and the clips were removed to obtain a laminate in which a cured layer was formed on the PET film. For Examples 21 and 22, laminates were obtained in the same manner as in Examples 12 to 20, except that the curable composition was applied using a bar coater No. 3 to give an uncured coating film having a dry thickness of 5 to 6 μm.
[0153] -Water resistance test- The laminate obtained above was used as a test article. The test article was immersed in ion-exchanged water at 23°C for 24 hours, and then removed from the water. Pure water was poured onto the surface using a wash bottle containing ion-exchanged water, and the test article was then air-dried at room temperature. The surface after air-drying was visually observed, and those that showed no change in the appearance of the surface (cured product) were marked with "○", those that were dissolved and disappeared, those that were partially swollen or peeled off, and those that did not maintain their original shape, or those that maintained their original shape but were whitened, were marked with "×". In Examples 12 to 22, since there was absolutely no change in appearance after air drying, the test articles were subjected to a water resistance test, and the breath anti-fogging properties, water contact angle, and pencil hardness were measured.
[0154] <Anti-fog breath performance after water resistance test> For the test articles that underwent the above-mentioned water resistance test, exhaled air was sprayed onto the surface of the test article for 3 seconds from a position 5 cm away from the surface of the test article in an environment of a temperature of 23°C and a humidity of 50%. Those that did not become cloudy were marked with an O, and those that did become cloudy were marked with an X.
[0155] <Water contact angle after water resistance test> For the test articles subjected to the water resistance test, the contact angles were measured under the following conditions 30 seconds and 3 minutes after a water droplet landed on the surface of the test article using an MSA Flex (KRUESS) contact angle meter. Measurement temperature: 23℃, humidity 50% Amount of pure water dispensed: 2μL Calculation of measured value: The static contact angle was measured at any three points on the surface of the test article by the θ / 2 method, and the average value was regarded as the water contact angle.
[0156] <Pencil hardness after water resistance test> For the test articles that had been subjected to the water resistance test, the pencil hardness was measured using an electric pencil hardness tester under a load of 750 g.
[0157] Example 1 In a screw tube containing a stirrer, 0.004g of a fluorine-based surfactant (Ftergent 215M, Neos Co., Ltd.), 1.4g of ultrapure water, 1.03g of 2-allyloxymethylacrylic acid, 0.50g of acrylic acid, and 0.38g of zinc oxide were weighed, and the mixture was stirred until transparent while heating to 50°C, and then 0.17g of calcium hydroxide was added and stirred until transparent. After returning to room temperature, 0.057g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a coating liquid (curable composition) with a solvent (water) content of about 45% by mass was obtained. The substances represented by the abbreviations shown in Table 1 are as shown in Table 2. Test articles were prepared using the prepared curable compositions, and the water resistance, breath anti-fogging properties, and water contact angle were evaluated. The results are shown in Table 1.
[0158] Example 2 In a screw tube containing a stirrer, 0.004g of a fluorine-based surfactant (Ftergent 215M, Neos Co., Ltd.), 1.45g of ultrapure water, 0.62g of 2-allyloxymethylacrylic acid, 0.91g of acrylic acid, and 0.48g of zinc oxide were weighed and heated to 50 ° C. and stirred until transparent. After returning to room temperature, 0.20g of sodium hydroxide was added and stirred. Finally, 0.060g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0159] Example 3 In a screw tube containing a stirrer, 0.004g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.65g of ultrapure water, 0.62g of 2-allyloxymethylacrylic acid, 0.91g of acrylic acid, and 0.48g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.25g of tris (2-aminoethyl) amine was added and stirred. Finally, 0.064g of 2-hydroxy-1- [4- (2-hydroxyethoxy) phenyl] -2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0160] Example 4 In a screw tube containing a stirrer, 0.004 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.65 g of ultrapure water, 0.62 g of 2-allyloxymethylacrylic acid, 0.91 g of acrylic acid, and 0.48 g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.24 g of polyethyleneimine (Epomin SP-300, Nippon Shokubai Co., Ltd.) was added and stirred. Finally, 0.064 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1 to obtain a curable composition with a solvent (water) content of about 45 mass%. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0161] Example 5 In a screw tube containing a stirrer, 0.005 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.95 g of ultrapure water, 0.44 g of 2-allyloxymethylacrylic acid, 1.08 g of acrylic acid, and 0.36 g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.66 g of N,N'-bis (2-hydroxyethyl) ethylenediamine was added and stirred. Finally, 0.074 g of 2-hydroxy-1- [4- (2-hydroxyethoxy) phenyl] -2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0162] Example 6 In a screw tube containing a stirrer, 0.004g of a fluorine-based surfactant (Ftergent 215M, Neos Co., Ltd.), 1.65g of ultrapure water, 0.44g of 2-allyloxymethylacrylic acid, 1.08g of acrylic acid, and 0.49g of zinc oxide were weighed, and the mixture was stirred until transparent while heating to 50°C, and then 0.17g of magnesium hydroxide was added and stirred until transparent. After returning to room temperature, 0.22g of polyvinylpyrrolidone (K-85, Nippon Shokubai Co., Ltd.) and 0.065g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) were added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45% by mass was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0163] Example 7 In a screw tube containing a stirrer, 0.006 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 2.6 g of ultrapure water, 0.44 g of 2-allyloxymethylacrylic acid, 1.08 g of acrylic acid, and 0.36 g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.66 g of N,N'-bis (2-hydroxyethyl) ethylenediamine was added and stirred, and then 0.54 g of glycerol monomethacrylate was added and stirred. Finally, 0.090 g of 2-hydroxy-1- [4- (2-hydroxyethoxy) phenyl] -2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0164] Example 8 Into a screw tube containing a stirrer, 0.007 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 2.4 g of ultrapure water, 0.44 g of 2-allyloxymethylacrylic acid, 1.08 g of acrylic acid, and 0.36 g of zinc oxide were weighed and stirred until transparent while heating to 50° C. After returning to room temperature, 0.66 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred, and then 0.56 g of glycerol monomethacrylate and 0.26 g of potassium 3-sulfopropyl acrylate were added and stirred. Finally, 0.098 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter with a pore size of 0.45 μm. The components were mixed in the mass ratio shown in Table 1 to obtain a curable composition with a solvent (water) content of approximately 45 mass%. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0165] Example 9 In a screw tube containing a stirrer, 0.007 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.4 g of ultrapure water, 2.2 g of 2-propanol, 0.44 g of 2-allyloxymethylacrylic acid, 1.08 g of acrylic acid, and 0.36 g of zinc oxide were weighed and heated to 50°C while stirring until the mixture became transparent. 0.66 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred until the mixture became transparent. After returning to room temperature, 0.56 g of glycerol monomethacrylate and 0.26 g of polyester acrylate (EBECRYL 810, Daicel Allnex Co., Ltd.) were added and stirred. Finally, 0.098 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The components were mixed in the mass ratio shown in Table 1 to obtain a curable composition with a solvent (water / 2-propanol mixed solvent) content of approximately 45 mass%. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0166] Example 10 2.0 g of ultrapure water, 0.44 g of 2-allyloxymethylacrylic acid, 1.08 g of acrylic acid, and 0.36 g of zinc oxide were weighed into a screw tube containing a stirrer, and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.27 g of ethylenediamine, 0.55 g of glycerol monomethacrylate, and 0.06 g of a radical polymerizable surfactant (Antox LMA-20, Nippon Nyukazai Co., Ltd.) were added and stirred. Finally, 0.078 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0167] Example 11 In a screw tube containing a stirrer, 1.7 g of ultrapure water, 1.7 g of 2-propanol, 0.51 g of 2-allyloxymethylacrylic acid, 1.28 g of acrylic acid, and 0.61 g of zinc oxide were weighed and stirred until the mixture became transparent while heating to 50°C, and 0.66 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred until the mixture became transparent. After returning to room temperature, 0.60 g of glycerol monomethacrylate, 0.30 g of potassium 3-sulfopropyl acrylate, 0.30 g of tetraethylene glycol diacrylate, 0.18 g of dipentaerythritol hexaacrylate, 0.18 g of polyglycerin-based acrylate (SA-TE6, Sakamoto Yakuhin Kogyo Co., Ltd.), and 0.06 g of radical polymerizable surfactant (Aminoion RE1000L, Nippon Nyukazai Co., Ltd.) were added and stirred. Finally, 0.125 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The components were mixed in the mass ratio shown in Table 1 to obtain a curable composition with a solvent (water / 2-propanol mixed solvent) content of approximately 45 mass%. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0168] Comparative Example 1 In a screw tube containing a stirrer, 0.004 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.5 g of ultrapure water, 1.03 g of 2-allyloxymethylacrylic acid, 0.50 g of acrylic acid, and 0.57 g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.064 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0169] Comparative Example 2 In a screw tube containing a stirrer, 0.004g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.55g of ultrapure water, 0.62g of 2-allyloxymethylacrylic acid, 0.91g of acrylic acid, and 0.69g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.061g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0170] Comparative Example 3 In a screw tube containing a stirrer, 0.003 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.1 g of ultrapure water, 0.62 g of 2-allyloxymethylacrylic acid, 0.91 g of acrylic acid, and 0.49 g of magnesium hydroxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.051 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0171] Comparative Example 4 In a screw tube containing a stirrer, 0.005g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 1.9g of ultrapure water, 0.62g of 2-allyloxymethylacrylic acid, 0.91g of acrylic acid, and polyethyleneimine (K-85, Nippon Shokubai Co., Ltd.) were weighed and stirred at room temperature until transparent. Then, 0.058g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45% by mass was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0172] Comparative Example 5 In a screw tube containing a stirrer, 0.005 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 2.0 g of ultrapure water, 0.44 g of 2-allyloxymethylacrylic acid, 1.08 g of acrylic acid, and 0.73 g of zinc oxide were weighed and stirred until transparent while heating to 50 ° C. After returning to room temperature, 0.52 g of glycerol monomethacrylate and 0.078 g of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Omnirad 2959, IGM Resins Co., Ltd.) were added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each component was mixed to obtain the mass ratio shown in Table 1, and a curable composition with a solvent (water) content of about 45 mass% was obtained. Test articles were prepared in the same manner as in Example 1, and the water resistance, breath anti-fogging property, and water contact angle were evaluated. The results are shown in Table 1.
[0173] Example 12 In a screw tube containing a stirrer, 0.009g of a fluorochemical surfactant (Ftergent 215M, Neos Co., Ltd.), 0.2g of methanol, 1.04g of 2-allyloxymethylacrylic acid, and 0.52g of N,N'-bis(2-hydroxyethyl)ethylenediamine were weighed out, and the mixture was stirred until transparent while heating to 50°C, and then 1.38g of methoxypolyethyleneglycol acrylate (NK Ester AM-230G, Shin-Nakamura Chemical Co., Ltd.) was added and stirred until homogenous. After returning to room temperature, 0.85g of 3-(trimethoxysilyl)propyl acrylate and 0.85g of polyethylene glycol diglycidyl ether with an average repeat number of polyethylene glycol chains of 2 (Denacol EX-850, Nagase Chemtex Co., Ltd.) were added and stirred to homogenize. Finally, 0.15 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each active ingredient was mixed in the mass ratio shown in Table 3 to obtain a curable composition with an active ingredient content of more than 90 mass %. The substances represented by the abbreviations shown in Table 3 are as shown in Table 4. The test article was prepared using the prepared curable composition as described above, and the breath antifogging property after the water resistance test, the water contact angle after the water resistance test, and the pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0174] Example 13 In a screw tube containing a stirrer, 0.007g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2g of methanol, 1.04g of 2-allyloxymethylacrylic acid, and 0.10g of zinc oxide were weighed out, and the mixture was stirred until transparent while heating to 50°C, and then 0.34g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred until homogenous. After returning to room temperature, 0.82g of 3-(trimethoxysilyl)propyl acrylate and 1.32g of polyethylene glycol diglycidyl ether with an average repeat number of polyethylene glycol chain of 9 (Denacol EX-830, Nagase ChemteX Co., Ltd.) were added and stirred to homogenize. Finally, 0.09 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0175] Example 14 In a screw tube containing a stirrer, 0.007 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 1.04 g of 2-allyloxymethylacrylic acid, and 0.10 g of zinc oxide were weighed out and heated to 50°C while stirring until the mixture became transparent. Then, 0.34 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred until the mixture was homogenized. After returning to room temperature, 0.82 g of 3-(trimethoxysilyl)propyl acrylate, 0.60 g of polyethylene glycol diglycidyl ether having an average repeat number of 2 polyethylene glycol chains (Denacol EX-850, Nagase ChemteX Corp.), and 0.71 g of polyethylene glycol diglycidyl ether having an average repeat number of 13 polyethylene glycol chains (Denacol EX-841, Nagase ChemteX Corp.) were added and stirred to homogenize. Finally, 0.09 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added and stirred until the powder was dissolved, and then filtered through a membrane filter with a pore size of 0.45 μm. Each active ingredient was mixed to obtain the mass ratio shown in Table 3, and a curable composition having an active ingredient content of more than 90 mass% was obtained. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0176] Example 15 In a screw tube containing a stirrer, 0.007 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 1.04 g of 2-allyloxymethylacrylic acid, and 0.11 g of zinc oxide were weighed out and heated to 50°C while stirring until the mixture became transparent. 0.31 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred until homogenized. After returning to room temperature, 0.82 g of 3-(trimethoxysilyl)propyl acrylate, 0.33 g of 3-glycidyloxypropyltrimethoxysilane, 0.26 g of trimethylolpropane polyglycidyl ether (Denacol EX-321, Nagase ChemteX Corp.), 0.33 g of polyethylene glycol diglycidyl ether with an average repeat number of polyethylene glycol chain of 9 (Denacol EX-830, Nagase ChemteX Corp.), and 0.13 g of lauryloxypolyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corp.) were added and stirred until homogenized. Finally, 0.09 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0177] Example 16 In a screw tube containing a stirrer, 0.007 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 1.04 g of 2-allyloxymethylacrylic acid, and 0.11 g of zinc oxide were weighed out and heated to 50°C while stirring until the mixture became transparent. 0.31 g of N,N'-bis(2-hydroxyethyl)ethylenediamine was added and stirred until homogenized. After returning to room temperature, 0.14 g of 2-ethylhexyl acrylate, 0.77 g of 3-(trimethoxysilyl)propyl acrylate, 0.35 g of 3-glycidyloxypropyltrimethoxysilane, 0.18 g of glycerol polyglycidyl ether (Denacol EX-313, Nagase ChemteX Corporation), 0.18 g of hydrogenated bisphenol A type epoxy resin (jER YX8000, Mitsubishi Chemical Corporation), 0.35 g of polyethylene glycol diglycidyl ether with an average repeat number of polyethylene glycol chain of 9 (Denacol EX-830, Nagase ChemteX Corporation), and 0.14 g of lauryloxy polyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation) were added and stirred until homogenized. Finally, 0.09 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0178] (Example 17) Into a screw tube containing a stirrer were weighed 0.004 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 0.85 g of 2-allyloxymethylacrylic acid, 0.18 g of acrylic acid, and 0.13 g of zinc oxide. The mixture was stirred while heating to 50°C until the mixture became transparent, and then 0.48 g of diallylamine was added while cooling in an ice bath and the mixture was stirred. After returning the mixture to room temperature, 0.40 g of 4-hydroxybutyl acrylate, 0.79 g of 3-(trimethoxysilyl)propyl acrylate, 0.32 g of 3-glycidyloxypropyltrimethoxysilane, 0.32 g of hydrogenated bisphenol A type epoxy resin (jER YX8000, Mitsubishi Chemical Corporation), 0.40 g of polyethylene glycol diglycidyl ether having an average repeat number of polyethylene glycol chains of 9 (Denacol EX-830, Nagase ChemteX Corporation), and 0.16 g of lauryloxypolyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation) were added and stirred to make a homogenous mixture. Finally, 0.11 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0179] (Example 18) Into a screw tube containing a stirrer were weighed 0.004 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 0.85 g of 2-allyloxymethylacrylic acid, 0.18 g of acrylic acid, and 0.13 g of zinc oxide. The mixture was stirred while heating to 50°C until the mixture became transparent, and then 0.48 g of diallylamine was added while cooling in an ice bath and the mixture was stirred. After returning the mixture to room temperature, 0.40 g of 4-hydroxybutyl acrylate, 0.79 g of 3-(trimethoxysilyl)propyl methacrylate, 0.32 g of 3-glycidyloxypropyltrimethoxysilane, 0.32 g of hydrogenated bisphenol A type epoxy resin (jER YX8000, Mitsubishi Chemical Corporation), 0.40 g of polyethylene glycol diglycidyl ether having an average repeat number of polyethylene glycol chains of 9 (Denacol EX-830, Nagase ChemteX Corporation), and 0.16 g of lauryloxypolyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation) were added and stirred to make a homogenous mixture. Finally, 0.11 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0180] (Example 19) Into a screw tube containing a stirrer were weighed 0.004 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 0.69 g of 2-allyloxymethylacrylic acid, 0.34 g of acrylic acid, and 0.19 g of zinc oxide. The mixture was stirred while heating to 50°C until the mixture became transparent, and then 0.46 g of diallylamine was added while cooling in an ice bath and the mixture was stirred. After returning the mixture to room temperature, 0.37 g of 4-hydroxybutyl acrylate, 0.64 g of 3-(trimethoxysilyl)propyl acrylate, 0.30 g of 3-glycidyloxypropyltrimethoxysilane, 0.30 g of hydrogenated bisphenol A type epoxy resin (jER YX8000, Mitsubishi Chemical Corporation), 0.37 g of polyethylene glycol diglycidyl ether having an average repeat number of polyethylene glycol chains of 9 (Denacol EX-830, Nagase ChemteX Corporation), and 0.15 g of lauryloxypolyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation) were added and stirred to make a homogenous mixture. Finally, 0.10 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0181] (Example 20) Into a screw tube containing a stirrer were weighed 0.004 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.2 g of methanol, 0.69 g of 2-allyloxymethylacrylic acid, 0.34 g of acrylic acid, and 0.19 g of zinc oxide. The mixture was stirred while heating to 50°C until the mixture became transparent, and then 0.46 g of diallylamine was added while cooling in an ice bath and the mixture was stirred. After returning the mixture to room temperature, 0.37 g of 4-hydroxybutyl acrylate, 0.64 g of 3-(trimethoxysilyl)propyl methacrylate, 0.30 g of 3-glycidyloxypropyltrimethoxysilane, 0.30 g of hydrogenated bisphenol A type epoxy resin (jER YX8000, Mitsubishi Chemical Corporation), 0.37 g of polyethylene glycol diglycidyl ether having an average repeat number of polyethylene glycol chains of 9 (Denacol EX-830, Nagase ChemteX Corporation), and 0.15 g of lauryloxypolyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation) were added and stirred to make a homogenous mixture. Finally, 0.10 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) was added, and the mixture was stirred until the powder was dissolved. The mixture was then filtered through a membrane filter having a pore size of 0.45 μm. The active ingredients were mixed in the mass ratios shown in Table 3 to obtain curable compositions with an active ingredient content of more than 90 mass%. Using the obtained curable composition, a test article was prepared in the same manner as in Example 12, and the breath antifogging property, water contact angle, and pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0182] Example 21 Into a screw tube containing a stirrer, 0.003 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.20 g of trishydroxymethylaminomethane, 0.49 g of 2-allyloxymethylacrylic acid, and 0.6 g of methanol were weighed out and heated to 50°C while stirring until the solid was completely dissolved. After returning the mixture to room temperature, 0.30 g of 3-aminopropyltrimethoxysilane was added and stirred. Next, 0.81 g of 4-hydroxybutyl acrylate, 0.65 g of 3-glycidyloxypropyltrimethoxysilane, 0.65 g of hydrolysis-polycondensation oligomer of tetramethoxysilane (MKC silicate MS51, Mitsubishi Chemical Corporation), 0.16 g of lauryloxypolyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation), and 0.06 g of 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM Resins) were added and stirred to homogenize. Separately, 0.20 g of 2-allyloxymethylacrylic acid, 0.21 g of diazabicycloundecene, and 0.40 g of ethyl acetate were weighed in a screw tube, shaken to homogenize, and then 0.38 g was taken and added to the screw tube containing the previously prepared curable composition and stirred. The mixture was filtered through a membrane filter having a pore size of 0.45 μm to obtain a curable composition having an active ingredient content of about 80 mass % in the weight ratio of the active ingredient as shown in Table 3. The test article was prepared using the prepared curable composition as described above, and the breath antifogging property after the water resistance test, the water contact angle after the water resistance test, and the pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0183] Example 22 Into a screw tube containing a stirrer, 0.003 g of a fluorosurfactant (Ftergent 215M, Neos Co., Ltd.), 0.37 g of trishydroxymethylaminomethane, 0.45 g of 2-allyloxymethylacrylic acid, and 0.6 g of methanol were weighed out and heated to 50°C while stirring until the solid was completely dissolved, and then the temperature was returned to room temperature. Next, 0.48 g of 4-hydroxybutyl acrylate, 0.32 g of glycerol monomethacrylate, 0.58 g of 3-glycidyloxypropyltrimethoxysilane, 0.77 g of hydrolysis-polycondensation oligomer of tetramethoxysilane (MKC Silicate MS51, Mitsubishi Chemical Corporation), 0.13 g of polyethylene glycol diglycidyl ether with an average repeat number of polyethylene glycol chain of 13 (Denacol EX-841, Nagase ChemteX Corporation), 0.13 g of lauryloxy polyethylene glycol glycidyl ether (Denacol EX-171, Nagase ChemteX Corporation), 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, IGM 0.06g of 2-allyloxymethylacrylic acid (Resins) was added and stirred to homogenize. Separately, 0.20g of 2-allyloxymethylacrylic acid, 0.21g of diazabicycloundecene, and 0.40g of ethyl acetate were weighed into a screw tube, shaken to homogenize, and 0.38g was taken and added to the screw tube containing the previously prepared curable composition and stirred. The mixture was filtered through a membrane filter with a pore size of 0.45μm to obtain a curable composition having an active ingredient content of about 80% by mass in the weight ratio of the active ingredient shown in Table 3. The test article was prepared using the prepared curable composition as described above, and the breath antifogging property after the water resistance test, the water contact angle after the water resistance test, and the pencil hardness after the water resistance test were evaluated. The results are shown in Table 3.
[0184] [Table 1]
[0185] [Table 2]
[0186] [Table 3]
[0187] [Table 4]
[0188] Tables 1 to 4 show that the cured products of the examples have both water resistance and hydrophilicity (breath anti-fogging property, water contact angle). Furthermore, the results of Examples 12 to 22 show that the use of a compound having an epoxy group and / or an alkoxysilyl group in combination can provide a cured product with high water resistance.
Claims
1. The following formula (1): 【Chemistry 1】 (In the formula, R represents a hydrogen atom or a methyl group.) The composition contains a 2-(meth)allyloxymethyl acrylate ion represented by the formula: The water resistance improving component includes at least one selected from the group consisting of a water-resistant polyvalent metal ion, a radical polymerizable compound having a hydrophilic functional group or structure, a polyfunctional radical polymerizable compound, a low-viscosity radical polymerizable compound, a compound that undergoes a thermal addition reaction or thermal condensation reaction with an active hydrogen group, and a resin having a hydrophilic functional group or structure. A curable composition comprising:
2. The curable composition of claim 1 , further comprising a surfactant.
3. A cured product of the curable composition according to claim 1 or 2.
4. A cured product of the curable composition according to claim 1 or 2, A water-insoluble cured product that satisfies at least one of the following index (I) and index (II): Index (I) Anti-fogging properties against breath Indicator (II) Water contact angle is 50° or less
5. An article having the cured product according to claim 3 on a surface thereof.
Citation Information
Patent Citations
Cation-polymerizable ultraviolet ray curing type composition for forming Anti-fogging coating film and molded article on whose surface cured coating film of the composition is formed
JP2007063325A
Antifogging agent
JP2011213904A
Antifogging coating composition
JP2012007033A
Diene-based carboxylate anion and salt thereof, and polymerizable or curable composition thereof
JP2012107208A
Polymerizable composition
JP2013216737A
Cited By
Flexible blocking agent for marine oil and gas drilling fluid as well as preparation method and application of flexible blocking agent
CN122145690A